2022
DOI: 10.1021/acs.inorgchem.2c01287
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Coordination Behavior of Methyl-Substituted Phosphinic Acids with Actinides

Abstract: The electronic structure and complexation behavior of methylsubstituted phosphinic acids with U(VI) and Pu(IV) were explored by applying quantum chemical methods. In contrast to Ingold's classification, our results indicate that the methyl group is electron-withdrawing, reducing the phosphoryl group electron density in substituted phosphinic acids. The magnitude of the computed complexation energy values increases along with the series, PA → MPA → DMPA, and MP → MMP → MDMP, implying an increasing complexation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The preliminary geometry optimizations yielded numerous structures with closely related geometries, exhibiting a relatively small energy difference of approximately 4–5 kcal/mol between each configuration (for details, see the Supporting Information). This outcome aligns with our findings from previous studies, , which have demonstrated that the C–C bond rotations are energetically favorable under ambient conditions. Furthermore, for ligand L 1 , we have obtained four energetically higher-lying structures (ca.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The preliminary geometry optimizations yielded numerous structures with closely related geometries, exhibiting a relatively small energy difference of approximately 4–5 kcal/mol between each configuration (for details, see the Supporting Information). This outcome aligns with our findings from previous studies, , which have demonstrated that the C–C bond rotations are energetically favorable under ambient conditions. Furthermore, for ligand L 1 , we have obtained four energetically higher-lying structures (ca.…”
Section: Resultssupporting
confidence: 93%
“…A triple-ζ basis set with two sets of polarization functions (TZ2P) was used for all of the atoms during this step. Note that the use of the BP86 functional for the EDA of lanthanide and actinide complexes is well documented. ,,, During the EDA computations, a two-fragment scheme was adopted with the metal nitrate forming one fragment and the ligands constituting the second fragment. Since our focus is on the interaction between the metal nitrate and the ligand at the interface of the aqueous and organic layers, leading to complexation, cation–cation (metal ion) and cation–anion (metal ion and nitrate ion) interactions are not explored in this work.…”
Section: Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step, we identified the ground state electronic structure of both Eu­(III) and Am­(III) metal centers to be septet with six unpaired electrons. It is known that trivalent lanthanides and actinides form complexes of 1:3 stoichiometry with the monodentate ligands. ,, However, for completeness, we have considered the 1:1, 1:2, and 1:3 complexes of Eu­(NO 3 ) 3 and Am­(NO 3 ) 3 with all seven ligands. Under each stoichiometry, five starting structures, which differ in the geometric distribution of the ligands around the metal ions, were considered for the geometry optimization of complexes, thus generating a total of 210 structures.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the metal–ligand complexation is one of the critical parameters in solvent extraction, the increased extraction behavior of the phosphorus compounds (vide supra) is typically correlated to the strength of the metal–oxygen bond formed during extraction 21–23 . Since these interactions are presumed to be donor–acceptor type, it was further speculated that the strength of the metal–oxygen bond is directly proportional to the availability of electron density on the binding atom (oxygen), generally remarked as the “basicity of phosphoryl oxygen.” 24 From this perspective, the extraction efficiency of structurally modified phosphoryl ligands, such as elongation of the alkyl chain length, introduction of branching, and so forth, are conventionally regarded as factors affecting the “basicity” of the binding atom (oxygen) 24,25 .…”
Section: Introductionmentioning
confidence: 99%